A STUDY ON THE APPLICATION OF CHARACTER BUILDING EDUCATION FOR SHORINJI KEMPO ATHLETES IN BONTANG CITY - Nuarham, Rizky Ramadhani; Wingkolatin, Wingkolatin; Warman, Warman (Unmul Civic Education Journal, 2022)
Studi About the Application of Warman Education Character Building to Shorinji Kempo Athletes in Bontang City The purpose of this research is to find out how efforts are to apply character bulding education to Shorinji Kempo athletes in Bontang City. This research uses a qualitative type of descriptive research. This study was conducted from February to May 2019. The subject of the research was coach and athlete Shorinji Kempo in Bontang City. Data collection techniques use observation, interviews, and documentation. The data analysis technique uses miles and huberman models. Data validity using data triangulation. The results showed that in implementing character building education, it was carried out through daily activities such as, gashuku, late sanctions, arranging footwear, cleaning DO-JO, reading promises and Shorinji Kempo pledges. these activities can foster the character of the korsa soul, be disciplined, independent, value achievements, and be religious. In describing these activities, several obstacles were found, namely coaches who have different backgrounds and experiences, insufficient funds, places and training times complained by athletes, to the athlete himself. The kendela can hinder the achievement of the final impact to the maximum.